Pembangunan Sistem Manajemen Informasi Klinik Psikologi Berbasis Web (Studi Kasus : Psycho Care Malang) - Fadhil Rizqullah Saniputra; Denny Sagita Rusdianto; Komang Candra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Information management is the main thing that must be met by an agency, company, and certain institutions, especially if you have a lot of data and complex. Information systems have been widely used in various fields in Indonesia, including the field of psychological accommodation. The number of children with special needs who have received education is 18%, around 300,000 children. From these data there are still 82% of children with special needs who have not yet received educational services in Indonesia (KEMDIKBUD, 2017). In the registration process is still implemented by the patient's parents come to the clinic and fill in the patient's personal data on a sheet of paper that takes 1 day in the process of filling out the data. The data will be stored in a special archive for these patients. In the process of inspection by employees, it takes at least 2 days for inspection, and 1 day to check inspection data by experts. Therefore, the authors undertake research by proposing the development of a psychology clinic information management system which includes recommendations for patient diagnosis. The writer uses prototyping model because in Psycho Care Malang clinic all activities are still done manually and there is no system or application whatsoever. This research resulted in unit testing with three sample experiments, integration testing with one sample experiment, and validation testing by testing all functional requirements resulting in a value of 100% valid and in efficiency testing with four test scenarios resulting in an increased value of 67.8%.